Hedge Ratio Variation Under Different Energy Market Conditions: New Evidence by Using Quantile–Quantile Approach - Barati, Karim; Sharif, Arshian Aslam; Gökmenoğlu, Korhan K. (Springer Nature, 2023)
In this research, we investigated the long-run and causal relationships between spot and futures prices of crude oil, natural gas, and gasoline using monthly data and considering the variables’ distribution. The quantile co-integration and quantile causality tests provided strong evidence for the long-run and causal relationships among the variables. Furthermore, we examined the optimal hedge ratio (OHR) at different quantiles of the series using the recently developed quantile on the quantile approach. For all three commodities, our results confirmed the asymmetric response of the spot market to the futures market. Furthermore, our findings show that in a bullish market and for a large positive shock, the value of OHR is significantly greater than one. We observed lower fluctuations in the OHR as the maturities of the futures contracts increased. We discuss the policy implications of our research in detail in the Conclusion section. © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.
6th International Conference on Banking and Finance Perspectives, ICBFP 2022 -- 2022-05-26 through 2022-05-27 -- Cuenca -- 291359
Keywords: Causality; Energy market; Futures market; Hedge ratio; Quantile-on-quantile (QQ) approach